Organic Syntheses 2010
DOI: 10.1002/0471264229.os087.36
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Synthesis of 5 H ‐Indazolo‐[3,2‐ B ]benzo[ d ]‐1,3‐Oxazine: Two Efficient Preparative Methods

Abstract: 2‐Nitrobenzaldehyde 2‐Aminobenzyl alcohol 2‐Picoline borane 5 H‐ Indazolo‐[3,2b]benzo[d]‐1,3‐oxazine 2‐Nitrobenzyl bromide Diisopropylethyl amine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Of the two isomers, 2 H -indazoles are less explored than 1 H -indazoles. 2 In previous reports, 3 our laboratory has demonstrated the utility of the Davis-Beirut reaction – an effective N,N -bond forming heterocyclization reaction – to deliver 3-alkoxy- 2H -indazoles, benzoxazin[3,2-b]-indazole, oxazolino[3,2-b]indazole, and a variety of other indazolo-fused hetero-cycles from 2-nitrobenzaldehyde or 1-(bromomethyl)-2-nitrobenzene.…”
mentioning
confidence: 99%
“…Of the two isomers, 2 H -indazoles are less explored than 1 H -indazoles. 2 In previous reports, 3 our laboratory has demonstrated the utility of the Davis-Beirut reaction – an effective N,N -bond forming heterocyclization reaction – to deliver 3-alkoxy- 2H -indazoles, benzoxazin[3,2-b]-indazole, oxazolino[3,2-b]indazole, and a variety of other indazolo-fused hetero-cycles from 2-nitrobenzaldehyde or 1-(bromomethyl)-2-nitrobenzene.…”
mentioning
confidence: 99%
“…12 It was also found that 5 H -indazolo[3,2- b ]benzo[ d ][1,3]-oxazines can be obtained in a one-pot reaction starting with o -nitrobenzaldehyde. 12e We envisaged that these methods (Scheme 1a/b) could be extended to the synthesis of a variety of novel heterocyclic analogs by, for example, introduction of a nitrogen atom in the benzo ring of 2 H -indazoles or in any of the rings fused to this benzo ring (Scheme 1c).…”
mentioning
confidence: 99%
“…12 It was also found that 5 H -indazolo[3,2- b ]benzo[ d ][1,3]-oxazines can be obtained in a one-pot reaction starting with o -nitrobenzaldehyde. 12e We envisaged that these methods (Scheme 1a/b) could be extended to the synthesis of a variety of novel heterocyclic analogs by, for example, introduction of a nitrogen atom in the benzo ring of 2 H -indazoles or in any of the rings fused to this benzo ring (Scheme 1c). Indeed, a host of unique heterocycles can be envisioned in which the pyrazole ring is the common denominator and we report here that a number of benzo-1,3-dioxolo-, benzothiazolo-, pyrido-, quinolino-fused 5 H -benzo[ d ]-pyrazolo[5,1- b ]-[1,3]-oxazines and 1 H -pyrazoles are accessible in moderate to high yields (35-88%) via this N,N -bond forming heterocyclization reaction.…”
mentioning
confidence: 99%
See 2 more Smart Citations